Written speech development - a cultural-historical approach to the process of reading and writing ability acquisition - Jabłoński, Sławomir (Psychology of Language and Communication, 2002)
The author presents his own model of reading and writing ability development based on Lev S. Vygotsky’s cultural-historical theory. The process of learning to read and write is regarded as a process of forming a new higher mental function. The function, termed “written speech”, is the effect of building a relation between speech sounds and graphic signs of writing and meaning. Written speech is created during a complicated and long-term developmental process. Just as the structure of every higher mental function, psychological function organization activated during reading and writing (the written speech structure) is changed during its maturation. Observed quality changes of written speech structure are the basis for identifying four specific stages in written speech development: (1) the natural stage, (2) the “naive” stage, (3) the outer stage, and (4) the inner stage. The paper also presents the process of written speech development in the context of human psychological system development. From this perspective, written speech is always dominated by a central mental function, such as perception, memory or thinking.
Keywords: higher mental function; cultural development; written speech; oral speech; stages of higher mental function development